Effects of free weights and free weights with elastic bands on power development during a bench press - Reynolds, T.; Finch, A.; Ariel, G. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to examine the effects of the use of elastic bands in addition to free weights on power development while performing a bench press at maximal speed. METHODS: Eight healthy division AA football players from Indiana State University were tested for their 1 RM during a bench press after signing an informed consent. On 2 testing sessions with 3 days rest, the subjects performed bench presses for maximal speed that consisted of 3 trials of 2 repetitions with 45% of their 1RM load and on the other test day the subjects used a similar weight but elastic sport bands were attached to each end of the bar. A tension load cell was used to determine the elastic stiffness of the band and the elastic range of the bands. Videographic records were recorded at 60 Hz from a transverse view of the subject performing a bench press. Data point markers representing the body's lifting configuration were digitized, transformed using a 2D-DLT, and digitally smoothed at 10Hz. RESULTS & DISCUSSION: The subjects' mean weight was 90.6±11.3kg, their mean bench press 1RM was 162.5±23.4kg and their testing weight which represented 45% of their 1RM was 75.6±9.9 kg. Statistically significant different mean vertical bar velocities of 115.6±15.3 for the free weight (FW) condition and 87.8±14.1 cm.s-1 for the compensatory band method (CM) were found (p=.001) (Figure 1). The mean peak bar power for the FW condition during the bench press was 103.2±31.6W and the elastic band group was 113.9±33.5W (p=.13). Although not statistically different, the elastic band group averaged 9.5% more peak power per lift. Significant differences (p=.001) in the mean bar power existed with the FW group generating a mean power of 74.5±19.1W and the band group produced 92.3±23.6W during the accelerative phase of the lift. This indicated that the addition of bands to the free weight, increased the power generation by 19% during the accelerative phase of the lift. The decelerative phase of the lift revealed significantly greater (p=.02) mean power output 89.2±21.4W (29%) for the elastic band assisted lifts than the FW (63.4±23.6W). CONCLUSIONS: The use of the elastic bands produced increases in the peak power output 9.5%, 19% mean power output during the accelerative phase, and 29% mean power during the decelerative phase of the bench press which would be beneficial for athletes participating in throwing events where high terminal velocities with weighted objects are desired.